2022
DOI: 10.1177/00207640221099415
|View full text |Cite
|
Sign up to set email alerts
|

Youth suicide and hospital-presenting suicide attempts: Examination of risk factors for multiple suicide attempts in adolescence

Abstract: Background: The suicide rate among adolescents around the world has increased rapidly. There are many risk factors for attempting suicide, but not all have been clarified yet. Therefore, it is very important to identify risk factors. This study evaluated adolescents with a history of suicide attempts and their association with chronic diseases. Besides, to check whether they attempted suicide multiple times. Other clinical features related to multiple suicide attempts were investigated. Method: This study used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Individuals describing their health status as poor registered significantly higher total SPS and sub-dimension scores than those describing it as moderate or good. In support of these findings, one study retrospectively investigating suicide attempts among adolescents with chronic disease showed that individuals with chronic diseases were at a greater risk of both single and multiple attempts at suicide, and had a 6.14-fold greater risk of multiple attempts than healthy individuals [28].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Individuals describing their health status as poor registered significantly higher total SPS and sub-dimension scores than those describing it as moderate or good. In support of these findings, one study retrospectively investigating suicide attempts among adolescents with chronic disease showed that individuals with chronic diseases were at a greater risk of both single and multiple attempts at suicide, and had a 6.14-fold greater risk of multiple attempts than healthy individuals [28].…”
Section: Discussionmentioning
confidence: 87%
“…Analysis of deaths from suicide in 2019 in the province where this research was conducted showed that gender rates were very similar to one another (male 22, female 18) [5]. Studies investigating the relationship between suicide and gender report that males are at greater risk [27,28]. However, there are also studies reporting more attempted suicides among women.…”
Section: Discussionmentioning
confidence: 94%
“…At the peripandemic assessment, we performed sample-weighted multivariable logistic regression for each outcome variable (i.e., SI, SP, SA) to compute adjusted odds ratios (AOR) and 95% CIs, controlling for covariates. Based on previous studies ( Choi et al, 2021 ; DeVylder et al, 2021 ; Greydanus et al, 2010 ; Oh et al, 2022 ; Tobore, 2019 ; Tubas et al, 2022 ), covariates included demographic variables (i.e., age, sex, gender, race/ethnicity, disability status, international, relationship, residence) and plausible risk factors (i.e., smoking and vaping status, chronic diseases). A 2-sided p < .05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%